Valence tautomerism in copper coordination chemistry - Himmel, Hans-Jörg (Inorganica chimica acta, 2018)
Valence tautomerism in coordination chemistry is currently intensely studied, and several seminal review articles discuss important aspects of its applications in catalysis and material science. This article does not intend to comprehensively review research in this field, but to highlight the quest for new redox-active ligands for the rational design of valence tautomeric copper complexes and the control of the barrier for intramolecular electron-transfer. Redox-active guanidines as emerging new ligands for this purpose are in the focus of the discussion, and are compared to the established oxolene-type ligands that also nature uses.
Gesehen am 22.06.2018
Available online 1 August 2017